2010
DOI: 10.1063/1.3337725
|View full text |Cite
|
Sign up to set email alerts
|

Differential pulsed eddy current sensor for the detection of wall thinning in an insulated stainless steel pipe

Abstract: A differential probe which is used in the pulsed eddy current (PEC) system has been fabricated for the detection of wall thinning of insulated pipelines in a nuclear power plant (NPP). The differential PEC probe consists of two hall sensors in a differential arrangement. The tested sample is a stainless steel of thickness variation from 1 to 5 mm, the flat side of the sample is laminated by a plastic insulation having a uniform thickness to simulate the pipelines in NPP. The PEC response to varying metal thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Traditional PEC signal features used for evaluating test piece properties and defect quantification can be classified as: time domain signal features [8,9], frequency spectrum features [10,11], principal components [12,13] and integral features [14,15]. Some specific features among those which have been found to be effective on ferromagnetic materials for defect detection are presented in [4,16] while features used for thickness estimation are discussed in [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional PEC signal features used for evaluating test piece properties and defect quantification can be classified as: time domain signal features [8,9], frequency spectrum features [10,11], principal components [12,13] and integral features [14,15]. Some specific features among those which have been found to be effective on ferromagnetic materials for defect detection are presented in [4,16] while features used for thickness estimation are discussed in [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…The PEC technique contains frequency-rich information and has the potential to detect properties in great depth. Three features of the signal, namely, the peak height, the time of occurrence of the first peak, and a characteristic zero-crossing time were found to characterize the measurand (thickness or conductivity) [7]. However, complicated and advanced signal processing and interpretation are required to abstract the features of the PEC signal and link these features explicitly to the sample conditions.…”
mentioning
confidence: 99%
“…Time-domain features, such as peak value, time to peak, rising time, and zero crossing time, are widely used [5,6]. Yang et al [7], and Angani et al [8] investigated the detection of fatigue cracks and thickness using the peak value. Xu et al [9] found that the time to peak feature is independent of lift-off distance and has good robustness.…”
Section: Introductionmentioning
confidence: 99%